Crisis, Disaster Management, and Resilience: A Multilevel Governance Analysis of Disaster Management Gaps in Indonesia - Faturrahman, ‎ (KnE Social Sciences, 2025)
Indonesia’s geographical conditions that make the country prone to natural disasters encourage the government to improve disaster management. The increasing frequency of disasters from year to year requires the government to continue to innovate and improve disaster risk reduction governance. Sustainable resilience is the way to prepare Indonesia for the uncertainty of natural disasters in the future. National Board for Disaster Management/ Badan Nasional Penanggulangan Bencana (BNPB) as the main guardian of disaster management has a series of disaster management systems and participation in global disaster management efforts. Even so, Indonesia’s natural disaster management governance still has many shortcomings. In several natural disasters, including the 2018 Palu earthquake, Indonesia’s natural disaster management governance has not been fully holistic. Both at the local and the regional scale, Indonesia’s disaster management is still fragmented, has minimal coordination, and lacks coherence. The AHA Center (The ASEAN Coordinating Centre for Humanitarian Assistance on Disaster Management) as a natural disaster coordination center in Southeast Asia still has a gap both institutionally and practically with the Regional Disaster Management Agency. This research will study the governance structure of Indonesia’s disaster management with a multi-level governance approach. It will analyze how power, responsibilities, and resources are distributed, and provide recommendations on multi-level governance between Indonesia and the Association of Southeast Asian Nations (ASEAN).